Decreasing Entropy in Thoughts and Evolution: Main Ability Related to Inside Nature - Hideaki Yanagisawa (Mediterranean Journal of Clinical Psychology, 2017)
Abstract: In general, religious Gods have been considered for phenomena that cannot be objectively explained, based on the concept that humans are either believers or nonbelievers. However, science-based Gods prevent the existence of religious alleles, since they do not discriminate these two types of humans. Thus, the purpose of the present study is to mathematically explain phenomena by classifying them into the following six categories: infinity, no, complete fixed, incomplete fixed, chaotic solutions, and random solutions. It also examines the relationship between incomplete fixed and chaotic states (which is continuous and can be explained by chaos theory) as well as the relationship between other solutions (which is not continuous). It has been shown that the necessary conditions in chaos theory include continuous covariation and three or more variables. Moreover, in phenomena that involve physical bodies, there is a relationship with gravitational waves, while in chaotic phenomena, electromagnetic waves exist. The results, based on the second law of thermodynamics, showed that phenomena can be explained not as an act of a religious God, but that of a science-based God. In addition, it indicated that science-based Gods can prevent the existence of religious alleles, since they do not discriminate these two types of humans (i.e., believers and nonbelievers).